From the Mediterranean to the Libyan Sahara. Chemical analyses of Garamantian glass. (June 2016) - Duckworth, Chloë N.; Mattingly, David J.; Smith, Victoria C.
Abstract: This paper presents the results of electron microprobe analysis of 124 samples of glass from sites in Libya, most from the Saharan oasis belt of the Wadi al-Ajal. Imported Roman vessel glass; beads; vitreous production waste; and Islamic glass bangles have all been analysed, and provide the first chemical information on glass from this region.